Unveiling the Interactions between Individual, Entrepreneurial and Organizational Resilience of Entrepreneurs with Disabilities - Tessier Dargent, Christel; Billion, Julien (Relations industrielles / Industrial Relations, 2025)
In this article, we aim to shed light on the multiple levels of resilience, i.e., the ability to withstand or bounce back from difficulties individually and collectively, and how these levels interact in the case of entrepreneurs with disabilities. The aim is to determine the patterns and processes in the complex dynamics between the three levels of resilience—individual, entrepreneurial and organizational—which the literature describes as important, but without clearly elucidating how they interrelate. This question is crucial: resilience appears to be an essential capability for individuals and organizations alike in an unprecedentedly complex, challenging and uncertain environment. We interviewed twenty entrepreneurs with disabilities in France and found that individual resilience translates into entrepreneurial resilience, which in turn strengthens organizational resilience, via identified characteristics, e.g., anticipation, adaptation and empathy. Entrepreneurial resilience may also feed back into individual resilience, thereby strengthening control, self-efficacy and identity. Capabilities for resilience can be assisted at each level by resilience tutors through emotional, financial or professional support. Because people with disabilities have to develop significant individual resilience capabilities, they may become resilient entrepreneurs who foster resilience and inclusion in their organizations.